(untitled) (Research, Society and Development, 2022)
Based on the recent and important decision of the Federal Supreme Court (STF) by which it determined that ICMS should not compose the concept of revenue or billing for purposes of measuring the PIS/COFINS calculation base, this article aims to analyze the legal reasons that demonstrate the real reasons for the unconstitutionality and/or illegality of including the ISSQN in the calculation bases of said contributions. To this end, the applied methodology is based on bibliographical research, involving the study of specialized doctrine in the matter, through consultation of books and articles by the most renowned authors, as well as the analysis of a recent decision of the superior court. In this regard, in view of the great impact that a decision of this magnitude causes on the public coffers, a significant legal divergence is assumed, which, in a way, significantly explains the fact that the judgment of this thesis, until now, has not yet been have occurred. However, the possibilities are relevant that the same jurisprudential position that modified our tax system, with regard to the non-incidence of ICMS on the PIS/COFINS calculation base, will also be applied to the ISSQN, in view of the legal similarity of the facts presented.